Pelatihan Perencanaan Pembangunan Desa Seruni Mumbul dalam Rangka Mendorong Pencapaian SDG’s di Lombok Timur - Jaka Anggara; Muhammad Dzul Fadlli; Adhitya Bagus Singandaru; Vici Handalusia; Baiq Saripta Wijimulawiani (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Regulations on the use of the budget by the Village Government are constantly changing. These changing regulations require village officials and the community to understand the latest regulations in order to be able to make development budget priorities, including for preparing programs that support the achievement of Sustainable Development Goals (SDG’s). Community Service Activities aim as a forum to provide understanding and knowledge to village officials about (a) the Concept and Definition of SDG's; (b) The role of the village in realizing SDG's; (c) Development planning to realize SDG's. In order to achieve these goals, the solution is to carry out counseling to participants using the lecture method accompanied by discussion. This activity was said to have run well and was successful as assessed by several indicators, namely: (1) The participants who attended were village officials and community leaders had understood the material presented. (2) The village government has a superior development plan in order to encourage the achievement of SDG's. Suggestions regarding this activity are (1) Teams can carry out activities at the same location in the form of development planning technical assistance so that programs can be developed to achieve SDG's; (2) Public participation needs to be increased in development planning.